BAHD acetyltransferase contributes to wound‐induced biosynthesis of oleo‐gum resin triterpenes in Boswellia. (28th July 2021) - Kumar, Aashish; Srivastava, Payal; Srivastava, Gaurav; Sandeep,; Kumar, Narendra; Chanotiya, Chandan S.; Ghosh, Sumit
SUMMARY: Triterpenes (30‐carbon isoprene compounds) represent a large and highly diverse class of natural products that play various physiological functions in plants. The triterpene biosynthetic enzymes, particularly those catalyzing the late‐stage regio‐selective modifications are not well characterized. The bark of select Boswellia trees, e.g., B. serrata exudes specialized oleo‐gum resin in response to wounding, which is enriched with boswellic acids (BAs), a unique class of C3α‐epimeric pentacyclic triterpenes with medicinal properties. The bark possesses a network of resin secretory structures comprised of vertical and horizontal resin canals, and amount of BAs in bark increases considerably in response to wounding. To investigate BA biosynthetic enzymes, we conducted tissue‐specific transcriptome profiling and identified a wound‐responsive BAHD acetyltransferase (BsAT1) of B. serrata catalyzing the late‐stage C3α‐ O ‐acetylation reactions in the BA biosynthetic pathway. BsAT1 catalyzed C3α‐ O ‐acetylation of αBA, βBA, and 11‐keto‐βBA in vitro and in planta assays to produce all the major C3α‐ O ‐acetyl‐BAs (3‐acetyl‐αBA, 3‐acetyl‐βBA, and 3‐acetyl‐11‐keto‐βBA) found in B. serrata bark and oleo‐gum resin. BsAT1 showed strict specificity for BA scaffold, whereas it did not acetylate the more common C3β‐epimeric pentacyclic triterpenes. The analysis of steady‐state kinetics using various BAs revealed distinct substrate affinity and catalytic efficiency. BsAT1 transcript expression coincides with increased levels of C3α‐ O ‐acetyl‐BAs in bark in response to wounding, suggesting a role of BsAT1 in wound‐induced biosynthesis of C3α‐ O ‐acetyl‐BAs. Overall, the results provide new insights into the biosynthesis of principal chemical constituents of Boswellia oleo‐gum resin. Significance Statement: Boswellia trees produce specialized oleo‐gum resin in response to wounding, which is enriched with a unique class of C3α‐epimeric pentacyclic triterpenes, known as boswellic acids that have received considerable attention as medicinal compounds, but the biosynthetic enzymes of boswellic acids are still largely unknown. Here, we report the identification and functional characterization of a wound‐responsive BAHD acetyltransferase which catalyzes regio‐selective acetylation of boswellic acids in the formation of principal chemical constituents of Boswellia oleo‐gum resin.